PENGARUH ORIENTASI SERVICE VALUE, INOVASI LAYANAN SERTA EXPERIENTAL MARKETING TERHADAP PEMASARAN KEWIRAUSAHAAN USAHA MAKANAN – MINUMAN (Studi Pada Outlet Go Food di Area Tembalang) - Eko Hadi Wahyono; Leonardo Budi Hasiholan (Jurnal Ekonomi dan Bisnis Kontemporer, 2016)
This study seeks to assess the relationship between Micro, Small and Medium Enterprises(MSME) variabel Experiental Marketing (EM), Orientasi Service Value (OSV) and ServiceInovation (IS) in develop for all business. In previous research , many researce explore thecompany that focus only on serice quality only. This study focus on the big amount of new outlet from Go Food and describe theindependent Variable as Experiental Marketing (EM), Orientasi Service Value (OSV) sertaInovasi Layanan (IL). Data were collected from Go Food in Tembalang Semarang, A total of35 were surveyed in the study through adopting tested survey questionnaires from the pastliterature. Correlation and regression analysis were used to test the hypotheses. Resultindicates that Experiental Marketing (EM), Orientasi Service Value (OSV) serta InovasiLayanan (IL) have a positive direct influence on entrepreneurrial marketingKeywords: Experiental Marketing (EM), Orientasi Service Value Layanan (IL).(OSV) , Inovasi